DESKRIPSI KASUS MALARIA DI KABUPATEN PURWOREJO TAHUN 2009 – 2013 - Annisa Rosada; Susiyanti Susiyanti (Buletin Keslingmas, 2015)
Malaria is an infectious disease of the blood parasite plasmodium which is transmitted by mosquitoAnopheles sp. Malaria cases in Purworejo in 2000 as many as 33 543 cases or API (Annual ParasiteIncidence) 43.7 ‰, to 2009 cases continue to decrease the number of cases or API 359 ‰ 0:47.Beginning in 2010 increased the number of cases 372 or API (Annual Parasite Incidence) 0:49 ‰,whereas in 2011 occurred in 1001 cases of malaria or API (Annual Parasite Incidence) 1:34 ‰. 547cases occurred in 2012 with the API (Annual Parasite Incidence) of 0.57 ‰. This study aims to determinethe description of cases of malaria in Purworejo over the last 5 years (2009-2013).The method used in this research is descriptive. The study was conducted by collecting secondarydata from the District Health Office Purworedjo which includes the data of malaria cases in 2009-2013and data on malaria control Purworejo.The results showed malaria cases in 2009-2013 were highest in 2011 and the Health Center is ahealth center Kaligesing with the highest case. Index cases were indegeneus identified more with thetype of parasite highest P.falcipharum the ring phase. Control program runs quite well but health centerwith stratification HCI (High Case Incidence) is always there every year, especially in the last 3 yearsHealth Center Kaligesing always with stratification HCI (High Case Incidence).The conclusion of this research is the possibility of persistence of malaria cases occur due togeographical barriers and the possibility of resistance (vector and parasite). From these results it isexpected that the District Health Office Purworejo further improve the early warning system and try analternative to the control of environmental modification.